Eviction processes and housing counseling services: Contributions from the Experience of a Housing and Meeting Information Point (PIVE) in Seville, Spain - Girado, Agustina (Millcayac - Revista Digital de Ciencias Sociales, 2025)
Following the 2008 real estate and financial crisis, Spain has experienced a major social upheaval concerning housing, prompting the development of diverse participatory efforts for habitat transformation. This paper examines the role of the "Diamantino" Housing and Meeting Information Point (PIVE) in Seville. Through a qualitative, ethnographically-informed methodology, we analyze the interplay between housing challenges, eviction proceedings, and housing advisory services, situating them within their historical and everyday contexts.